Implementasi Metode Fun Learning dalam Pembelajaran Bahasa Arab untuk Meningkatkan Minat Belajar Siswa - Fatimatus Zahro, Nur Diana; Firdaus, Sulton (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
Arabic language learning currently challenges increasing students' interest and understanding, especially at the junior high school level. One of the factors that influences the effectiveness of Arabic language learning is the use of appropriate learning methods. This study aims to analyze the implementation of the fun learning method in Arabic language learning to increase the interest in learning of class IX students of MTs Nurul Falah. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects of the study consisted of Arabic language teachers and students involved in learning using the fun learning method. The results of the study indicate that the fun learning method has a very important role in increasing the effectiveness and involvement of students. The learning method in the form of chain word guessing or games with guessing sports with the concept of smart and careful in groups can make the learning process more interesting, fun, and interactive MTs Nurul Falah. These findings indicate that the fun learning method has been running well and even this method should continue to be maintained to increase the effectiveness of Arabic language learning in MTs schools.